Perceptions of Pharmacy Students on the E-Learning Strategies Adopted during the COVID-19 Pandemic: A Systematic Review - Carla Pires (MDPI AG, 2022)
Background: E-learning strategies were globally adopted by academies because of the COVID-19 pandemic. The characterization of students' perception of online learning is fundamental to design appropriate models for pharmacy curricula. The study aim was to carry out a systematic review about the perception of pharmacy students on the e-learning strategies adopted during the COVID-19 pandemic. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist was followed. PICOS criteria were applied. Five databases were screened: PubMed, Cochrane Library, DOAJ-Directory of Open Access Journals, SciELO-Scientific Electronic Library Online and b-on-Online Library of knowledge (Biblioteca do conhecimento online). Keywords: "pharmacy and (distant or remote or e-learning or online or zoom or education or training or digital) and (COVID or SARS and (student or undergraduate) and (opinion or satisfaction or perception or attitude)". Results: 23 out of 176 papers were selected (28 duplicated and 125 excluded). Selected papers were classified, as follows: studies exclusively involving pharmacy students (n = 8); studies simultaneously involving pharmacy students and other healthcare students (n = 6); and studies related to the involvement of pharmacy students in specific courses (n = 9). Conclusions: In general, the perception of pharmacy students on e-learning strategies adopted during the COVID-19 pandemic was positive. However, an expressive proportion of undergraduates reported negative issues about online education, which seems to support the necessity of optimizing e-learning strategies in the future.